2023
DOI: 10.1093/hmg/ddac308
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase deficiency and high-dose FA supplementation disrupt embryonic development of energy balance and metabolic homeostasis in zebrafish

Abstract: Folic acid (synthetic folate, FA) is consumed in excess in North America and may interact with common pathogenic variants in methylenetetrahydrofolate reductase (MTHFR); the most prevalent inborn error of folate metabolism with wide ranging obesity-related comorbidities. While preclinical murine models have been valuable to inform on diet-gene interactions, a recent Folate Expert panel has encouraged validation of new animal models. In this study, we characterized a novel zebrafish model of mthfr deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…MTHFR is the rate-limiting enzyme that catalyses the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate. 76,77 A study showed that increasing the concentration of unmetabolised folic acid could decrease the number and cytotoxicity of NK cells. 78 In addition, the polymorphisms of MTHFR could influence the regulation of immune cells.…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 99%
“…MTHFR is the rate-limiting enzyme that catalyses the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate. 76,77 A study showed that increasing the concentration of unmetabolised folic acid could decrease the number and cytotoxicity of NK cells. 78 In addition, the polymorphisms of MTHFR could influence the regulation of immune cells.…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 99%
“…Accurately measuring FI in zebrafish studies is critical. Previously described methods have included video imaging (e.g., by feeding fish flakes or Paramecia to which fluorescent dyes have been added to measure internalized fluorescence [50,69,73,80,85] or by using photometric assays to measure the orange-red color of fish after feeding brine shrimp [59]) or feed particle or Artemia nauplii consumption counting [56,62,70,72,74]. Other authors only considered the time fish spent feeding [53,65].…”
Section: Zebrafish Feed Intake: How Much Do They Eat?mentioning
confidence: 99%